2017
DOI: 10.1016/j.midw.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration of midwives in primary care midwifery practices with other maternity care providers

Abstract: Inter-professionals relations in maternity care in the Netherlands can be enhanced, especially the primary care midwives' interactions with physicians and with maternity care providers in the northern and central part of the Netherlands, and in urban areas. Future exploratory or deductive research may provide additional insight in the collaborative practice in everyday work setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
2
16
0
1
Order By: Relevance
“…Relatively similar findings were obtained in studies done in Saudi Arabiya (59.5%), Canada (moderate collaboration obtained) and Tigray Ethiopia (60%) [25][26][27]. But this finding is inconsistent with (showed better collaboration) than studies done in the Netherlands (38.4%), Iran (10.5%) and Ethiopia (41%) [10,12,13]. Better collaboration than this study was obtained in a study conducted in Malaysia (91.8%) [24].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Relatively similar findings were obtained in studies done in Saudi Arabiya (59.5%), Canada (moderate collaboration obtained) and Tigray Ethiopia (60%) [25][26][27]. But this finding is inconsistent with (showed better collaboration) than studies done in the Netherlands (38.4%), Iran (10.5%) and Ethiopia (41%) [10,12,13]. Better collaboration than this study was obtained in a study conducted in Malaysia (91.8%) [24].…”
Section: Discussionsupporting
confidence: 74%
“…It is demonstrated in two different studies that more than half of nurses and midwives exhibited noncollaborative behaviors and generally had not a good collaboration with physicians [10,11]. Another study conducted in Iran indicated that near half (48%) of nurses reported their remarks concerning the patient's health are ignored by physicians [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,18 This has required time, integration of services and enhanced interdisciplinary collaboration on many levels. 19 This has been recommended in New Zealand, 20 but there has been limited progress in implementing these recommendations. 21 MatCHAT has potential to support screening if attitude and operational barriers can be overcome.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of integrated care is seen as a means to overcome the negative experiences arising from referrals. To integrate maternity care services in the Netherlands, optimization of the coordination and collaboration between the three divisions is needed ( Boesveld et al, 2017;Haggerty et al, 2003;KNOV, 2016;Warmelink et al, 2017 ). Initiatives like the development of obstetric partnerships were set up to stimulate collaboration and better align the different maternity care practices ( de Boer and Zeeman, 2008 ).…”
Section: Introductionmentioning
confidence: 99%